Anterior cruciate ligament laxity related to the menstrual cycle: an updated systematic review of the literature - Belanger, L.; Burt, D.; Callaghan, J.; Clifton, S.; Gleberzon, B. J. (The Journal of the Canadian Chiropractic Association, 2013)
Objectives: The purpose of this study was to conduct a systematic review regarding the purported differences in anterior cruciate ligament (ACL) laxity throughout the course of the menstrual cycle.